Cardiac SPECT system with trajectory optimization (2013)
In a disclosed imaging method, the instantaneous speed or data acquisition dwell times of a detector head is optimized as a function of position along a path of the detector head around a subject. The optimization is respective to an expected radioactive emission profile of a region of interest that is less than the entire subject. The detector head is traversed along the path using the optimized instantaneous speed or data acquisition dwell times. During the traversing, imaging data are acquired using the detector head. The acquired imaging data are reconstructed to generate a reconstructed image of at least the region of interest. A gamma camera configured to perform the foregoing imaging method is also disclosed.